Remote Ischemic Conditioning in Ischemic Stroke and Myocardial Infarction: Similarities and Differences - Saccaro, Luigi F.; Aimo, Alberto; Emdin, Michele; Pico, Fernando (Frontiers in Neurology, 2021)
Acute myocardial infarction and ischemic stroke are leading causes of morbidity and mortality worldwide. Although reperfusion therapies have greatly improved the outcomes of patients with these conditions, many patients die or are severely disabled despite complete reperfusion. It is therefore important to identify interventions that can prevent progression to ischemic necrosis and limit ischemia-reperfusion injury. A possible strategy is ischemic conditioning, which consists of inducing ischemia – either in the ischemic organ or in another body site [i.e., remote ischemic conditioning (RIC), e.g., by inflating a cuff around the patient's arm or leg]. The effects of ischemic conditioning have been studied, alone or in combination with revascularization techniques. Based on the timing (before, during, or after ischemia), RIC is classified as pre-, per-/peri-, or post-conditioning, respectively. In this review, we first highlight some pathophysiological and clinical similarities and differences between cardiac and cerebral ischemia. We report evidence that RIC reduces circulating biomarkers of myocardial necrosis, infarct size, and edema, although this effect appears not to translate into a better prognosis. We then review cutting-edge applications of RIC for the treatment of ischemic stroke. We also highlight that, although RIC is a safe procedure that can easily be implemented in hospital and pre-hospital settings, its efficacy in patients with ischemic stroke remains to be proven. We then discuss possible methodological issues of previous studies. We finish by highlighting some perspectives for future research, aimed at increasing the efficacy of ischemic conditioning for improving tissue protection and clinical outcomes, and stratifying myocardial infarction and brain ischemia patients to enhance treatment feasibility.